Chemical composition, antioxidant capacity, and thermal behavior of Satureja hortensis essential oil - Dorina Rodica Chambre (Nature Portfolio, 2020)
Abstract Satureja hortensis is one of the representative plants from the Lamiaceae family, and its essential oil has been used in various applicative fields, from the food industry to aromatherapy. The changes that occur in heated samples at different temperatures (160, 175, 190 ºC) over different periods (0.5 and 2.5 h) in Satureja hortensis essential oil composition and chemical properties were evaluated. The results showed that the major chemical composition constituents of the investigated essential oil are γ-terpinene + α-terpinolene and carvacrol + p-cymene and the thermal behavior is dependent on the content. This composition drastically changes through the heating of the samples and causes significant changes in thermal behavior. The present study demonstrated that the concentration of carvacrol in S. hortensis essential oil is increasing after heating treatment, and the sample heated at 190 ºC for 2.5 h contained more than 91% carvacrol. This simple treatment is a rapid way to obtain carvacrol from the essential oil that has high potential as a natural preservative suitable for the food industry and alternative and complementary medicine.